The Effect of Modality and Narration Style on Recall of Online Health Information: Results From a Web-Based Experiment - Bol, Nadine; van Weert, Julia CM; de Haes, Hanneke CJM; Loos, Eugene F; Smets, Ellen MA (JMIR Publications, 2015)
BackgroundOlder adults are increasingly using the Internet for health information; however, they are often not able to correctly recall Web-based information (eHealth information). Recall of information is crucial for optimal health outcomes, such as adequate disease management and adherence to medical regimes. Combining effective message strategies may help to improve recall of eHealth information among older adults. Presenting information in an audiovisual format using conversational narration style is expected to optimize recall of information compared to other combinations of modality and narration style. ObjectiveThe aim of this paper is to investigate the effect of modality and narration style on recall of health information, and whether there are differences between younger and older adults. MethodsWe conducted a Web-based experiment using a 2 (modality: written vs audiovisual information) by 2 (narration style: formal vs conversational style) between-subjects design (N=440). Age was assessed in the questionnaire and included as a factor: younger (<65 years) versus older (≥65 years) age. Participants were randomly assigned to one of four experimental webpages where information about lung cancer treatment was presented. A Web-based questionnaire assessed recall of eHealth information. ResultsAudiovisual modality (vs written modality) was found to increase recall of information in both younger and older adults (P=.04). Although conversational narration style (vs formal narration style) did not increase recall of information (P=.17), a synergistic effect between modality and narration style was revealed: combining audiovisual information with conversational style outperformed combining written information with formal style (P=.01), as well as written information with conversational style (P=.045). This finding suggests that conversational style especially increases recall of information when presented audiovisually. This combination of modality and narration style improved recall of information among both younger and older adults. ConclusionsWe conclude that combining audiovisual information with conversational style is the best way to present eHealth information to younger and older adults. Even though older adults did not proportionally recall more when audiovisual information was combined with conversational style than younger adults, this study reveals interesting implications for improving eHealth information that is effective for both younger and older adults.